Geographic Information Systems (GIS) Application for Tsunami Inundation Modeling in Bantul Regency, Yogyakarta - Putu Perdana Kusuma Wiguna (Prodi Pendidikan Teknik Informatika Universitas Pendidikan Ganesha, 2014)
Tsunami(s) are natural disasters generated by abrupt, large disturbance of ocean bottom such as earthquakes, volcanic eruptions, landslides, or meteor impacts which creates high ocean waves. Tsunami events has devastating effects, especially to population which highly exposed by tsunami. This research conducted in Bantul Regency, Yogyakarta Province, Indonesia. The geomorphologic conditions and location of Bantul Regency makes Bantul becomes vulnerable to tsunami hazard triggered by earthquakes originated from subduction of the Indian-Australian Plate and Eurasian Plate in the Indian Ocean. This research applied Geographic Information Systems (GIS) modeling methods based on Digital Elevation Data (DEM) and tsunami inundation scenario of 5 meter, 7.5 meter and 10 meter. The model is built using ‘neighbourhood operations’ and ‘iteration’ processes using ILWIS software. The results of this research are tsunami inundation map in Bantul Regency, area of landuse exposed by tsunami events, and number of population impactedby tsunami inundation in Bantul Regency. The total of inundated area in the 5 meter inundation model is 38.13 km2, followed by 42.93 km2 for the 7.5 meter model and 76.02 km2 for the 10 meter model. Majority of landuse impacted by tsunami are settlements and ricefields. 5 meter inundation model reach 2,328 meter to land from 0 meter start, the 7.5 meter model reach 4,141 meter and 10 meter model reach 4,844 meter. There are 5 Sub-districts that really impacted by tsunami, i.e. Kretek, Sanden, Srandakan, Bambanglipuro and Pundong. Srandakan, Sanden and Kretek. Total of population impacted by tsunami reached 60572 in the 10 meter inundation model. Meanwhile, total 0f 8165 residents impacted from tsunami with 5 meter inundation model and 43088 residents from 10 meter model. The highest number of population impacted by tsunami is in Sanden, with total 25528 residents.